Bawaslu's role in handling violations of the regional head elections of re-gents and deputy regents in Serang district in 2024 - Asnawi, Asnawi; Pramono, Aris Seyanto; Safiullah, Safiullah (LEGAL BRIEF, 2025)
Regional Head Elections (Pilkada) are an important part of Indonesia's democratic system. However, in practice, various violations often occur that threaten the integrity of elections, particularly administrative violations involving election organizers, election participants, and local government officials. This study aims to analyze the role of the Election Supervisory Agency (Bawaslu) in addressing administrative violations during the 2024 Pilkada in Serang District, as well as to identify the challenges and effectiveness of its handling mechanisms. The method used is descriptive qualitative research with purposive sampling techniques for selecting key informants. Data was collected through in-depth interviews, document analysis, and indirect observation. The research was conducted from February to June 2025 with a total of 12 informants comprising representatives from Bawaslu, Panwascam, KPU, academics, and election observers. The results of the study show that Bawaslu Serang Regency has carried out its supervisory function through preventive, curative, and repressive approaches, although it still faces obstacles in terms of evidence, limited executive authority, and low community involvement. There were 37 cases of violations handled, with the most common categories involving money politics and the lack of neutrality among village officials. Some cases have been referred to the Election Violation Investigation Agency (Gakkumdu), the Civil Service Commission (KASN), and related institutions. This study concludes that the role of the Election Supervisory Agency is significant but not yet optimal due to weak structural and legal support. Strengthening institutional capacity and reforming the mechanisms for handling violations are necessary to ensure more integrity in future elections.